'What does that mean?': a qualitative exploration of the primary and secondary clinical care experiences of young people with continence problems in the UK. Issue 10 (16th October 2017) - Whale, Katie; Cramer, Helen; Wright, Anne; Sanders, Caroline; Joinson, Carol
Abstract : Objectives: To explore the clinical care experiences of young people with continence problems. Design: In-depth semistructured qualitative interviews were conducted by Skype and telephone, with the addition of art-based participatory research techniques. Transcripts were analysed using inductive thematic analysis. Setting: Primary and secondary care in the UK. Participants: We interviewed 20 participants (9 females, 11 males) aged 11–20 years. There were six participants with bedwetting alone, five with daytime wetting alone, five with combined (day and night) wetting and four with soiling. Results: We identified four themes: appointment experiences, treatment experiences, engagement with treatment and internalisation and externalisation of the continence problem. Patient-focused appointments using age-appropriate language were highly desirable. Continuity of care was highlighted as an important aspect of positive clinical experiences; however, this was found to be rare with many participants seeing a different person on each visit. Participants had tried a wide range of treatments for their continence problems with varying degrees of success. Relapse and treatment failure were common. Experiencing relapse was distressing and diminished participants' belief in the success of future treatments and undermined adherence. Participants would be seen to adopt two opposing coping strategies for dealing with their continence problem— internalisation and externalisation. Conclusion: Incontinence in young people is challenging to manage. Young people may need to try a range of treatments before their symptoms improve. Due to challenges in treatment, there is an increased risk of poor adherence. During patient-focused appointments, clinicians should work to build rapport with patients and use age-appropriate language. Involving young people in their own care decisions is important. The way in which young people understand their continence problem can influence their coping strategies and adherence to treatment regimes.